PRAKTIKALITAS E-LKPD BERBASIS STEM-PjBL DALAM PEMBELAJARAN IPA FASE B - Martatiyana, Diana Rossa; Nasbey, Hadi; Utami, Nidya Chandra Muji (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2024)
The presentation of LKPD, especially in science learning, needs to experience innovation, including the use of technology to improve the quality of learning, namely by developing E-LKPD. Previous research has developed a STEM-PjBL based Science E-LKPD, but the response of class IV students to the E-LKPD is not yet known. This research aims to determine students' responses to STEM-PjBL-based Science E-LKPD. This research uses qualitative data and quantitative data. The research results were obtained based on the results of the student and teacher response instruments to the STEM-PjBL based Science E-LKPD which got an average percentage of 83% on the one to one test UI and the students' response results got an average percentage of 95% with very good category in small group trials, and teacher responses were 93%, all of which reflect suitability and excellence in various important aspects of learning.